STRATEGI PEMASARAN RUMAH MAKAN SAUNG KABOGOH MELALUI SOCIAL MEDIA INSTAGRAM CABANG NAGASARI KARAWANG - Ade Eka Puspitasari; Dini Yani; Puji Isyanto; Sri Yanthy Yosepha (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2023)
The rapid development of technology means that business actors must also be quick to adjust to these changes, one form of technology that is widely used by people is social media. The number of active social media users in Indonesia in January 2022 grew by 12.35% from last year. More precisely, the number of active social media users in early 2022 is 191 million people, while in 2021 there will be 170 million people. Social media is the most widely used by Indonesian people where the percentage reaches 88.7%. In second and third positions are Instagram and Facebook with respective percentages of 84.8% and 81.3%. Marketing is an important part of running a business. There needs to be good management so that the business can grow and develop better and be able to compete with its competitors. One of the important elements in marketing is marketing strategy and marketing mix. A marketing strategy is needed so that market segments, target market determination, and market positioning can be selected correctly. Utilization of social media can provide conveniences in the promotion and buying and selling process carried out by MSMEs with their consumers and can minimize costs. However, to do this, seriousness must be taken in utilizing social media, namely having to give more or intensive time in managing marketing through social media. Saung Kabogoh Restaurant is a typical Sundanese restaurant which is located at Jl. Siliwangi, Nagasari Village, West Karawang District. This restaurant was established in November 2020, with 30 employees and 8 branches spread across Karawang and its surroundings.Keywords: Social Media, Marketing, Marketing Strategy, Saung Kabogoh Restaurant